Spontaneous bacterial peritonitis. Issue 980 (5th June 2007) - Koulaouzidis, A; Bhat, S; Karagiannidis, A; Tan, W C; Linaker, B D
Abstract : Spontaneous bacterial peritonitis (SBP) is the infection of ascitic fluid in the absence of any intra-abdominal, surgically treatable source of infection. Despite timely diagnosis and treatment its reported incidence in ascitic patients varies between 7–30%. Ascitic paracentesis remains the chief diagnostic procedure. Automated cell counters have the same diagnostic accuracy as the manual measurement of white cells. Lately, the use of leucocyte reagent strips (dipsticks) has emerged as a useful alternative. Examination of the fluid is not complete unless the sample is inoculated in blood culture bottles. Treatment is currently with third-generation cephalosporins or oral quinolones. Following a single episode of SBP patients should have long term antibiotic prophylaxis.